Interactive Storytelling 8th International Conference on Interactive Digital Storytelling, ICIDS 2015, Copenhagen, Denmark, November 30 - December 4, 2015, Proceedings - Schoenau-Fog, Henrik; Bruni, Luis Emilio; Louchart, Sandy; Baceviciute, Sarune; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 8th International Conference on Interactive Digital Storytelling, ICIDS 2015, held in Copenhagen, Denmark, in November/December 2015. The 18 revised full papers and 13 short papers presented together with 9 posters, 9 workshop descriptions, and 3 demonstration papers were carefully reviewed and selected from 80 submissions. The papers are organized in topical sections on theoretical and design foundations, technical advances, analyses and evaluation systems, and current and future usage scenarios and applications.
Keywords: Computer science; Arts; User interfaces (Computer systems).; Artificial intelligence; Application software; Personal computers; Multimedia systems; Computer Science; Computer Appl. in Arts and Humanities; Personal Computing; Media Design; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Arts; Electronic books